EXPLODING THE ROLE OF RELIGIOUS INSTITUTIONS IN COMBATING CHILD TRAFFICKING IN NIGERIA - Alhaji Umar Alkali; Laminu Bukar; Goni Usman Ansari (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2014)
Human trafficking is a global challenge especially in the 21stCentury. Nigeria like most developing countries is doing its best in addressing the menace of child trafficking. In view of the fact that religious institutions are highly respected in Nigeria, this paper intends to adopt a doctrinal methodology in examining the menace of child trafficking in Nigeria, by using the perspective of Islam and Christianity. Moreover, also seeing the role that can be played by the Supreme Council of Islamic Affairs and the Christian Association of Nigeria in the crusade against child trafficking in Nigeria Perdagangan manusia merupakan sebuah tantangan global pada abad ke-21. Sebagaimana negara berkembang pada umumnya, Nigeria melakukan upaya yang terbaik guna menangani ancaman perdagangan anak. Mengingat bahwa institusi keagamaan sangat dihormati di Nigeria, artikel ini bermaksud untuk mengadopsi metodologi doktrin dalam mengkaji ancaman perdagangan anak di Nigeria, melalui perspektif agama Islam dan agama Kristen perihal perdagangan anak. Selain itu, juga melihat peran yang dipegang oleh Dewan Tinggi Urusan Islam dan Asosiasi Umat Kristen Nigeria dalam perjuangan melawan perdagangan anak di Nigeria.